Biofilm formation capacity and Carbapenem-resistance in Acinetobacter-calcoaceticus-baumannii isolated from inpatients in a tertiary care hospital in Nepal - Shova Bhandari; Milan Kumar Upreti; Khadga Bikram Angbuhang; Basudha Shrestha; Upendra Thapa Shrestha (BMC Research Notes)
Abstract Objective Acinetobacter calcoaceticus-baumannii complex (ACBC), as an emerging global burden to various clinical infections, has a huge problem in empirical therapy due to the increasing resistance to the majority of antibiotics. The ability of biofilm formation added to its antimicrobial resistance and helped its persistence and survival in the environment. To associate biofilm formation with carbapenem resistance, a hospital-based cross-sectional study was carried out from February 2020 to August 2020 at Kathmandu Model Hospital, Kathmandu, Nepal. ACBC was identified from the clinical samples following standard Microbiological procedures. A modified Kirby-Bauer disk diffusion method was performed to assay the antibiotic susceptibility testing of ACBC isolates to various antibiotic classes. A quantitative adherence assay was used to determine the biofilm assay. A conventional Polymerase Chain Reaction (PCR) method was used to find the targeted biofilm-related genes, Bap, csuE, and bla PER1 using specific primers. Results Out of 665 different clinical samples, bacterial growth was observed in 281 (42.3%) clinical samples. Of these, 32 (11.4%) isolates were identified as ACBC. Out of 32 ACBC isolates, 29 (90.6%) of which were carbapenem-resistant. All carbapenem-resistant ACBC isolates were found to be sensitive to Polymixin B and Colistin. Out of 29 CR-ACBC, 17.2% of isolates were resistant to Tigecycline. The majority of ACBC isolates (93.8%) were multidrug-resistant (MDR) while 13 (40.6%) of isolates were extensively drug-resistant (XDR). A total of 31 ACBC isolates were biofilm producers, out of which 2 were strong biofilm producers followed by 8 moderate, and 21 were weak biofilm producers. The occurrence of biofilm-forming genes; Bap, csuE, and bla PER1 genes were found to be 65.6%, 65.6%, and 56.3% respectively among ACBC clinical isolates. A significant association was observed between carbapenem resistance, biofilm formation, and biofilm-related genes. Conclusion The higher rate of MDR and XDR ACBC isolates associated with biofilm formation in the study alarms the ACBC-related infection in clinical settings among inpatients. The hospital environment and clinical equipment are potential sources of biofilm-forming isolates. Hence, the effective sterilization of clinical equipment and hospital environment are utmost and a strong policy should be made to prescribe the proper antibiotic based on antibiogram profile to fight against an emerging threat of ACBC infections.